Long Non-coding RNA HIX003209 Promotes Inflammation by Sponging miR-6089 via TLR4/NF-κB Signaling Pathway in Rheumatoid Arthritis - Yan, Shushan; Wang, Pingping; Wang, Jinghua; Yang, Jinghan; Lu, Hongying; Jin, Chengwen; Cheng, Min; Xu, Donghua (Frontiers in Immunology, 2019)
Accumulating studies have suggested long noncoding RNAs (lncRNAs) have drawn more and more attention in rheumatoid arthritis (RA), which can function as competitive endogenous RNAs (ceRNAs) in inflammation and immune disorders. Previously, we have found lncRNA HIX003209 is differentially expressed in RA. However, the precise mechanism of lncRNA HIX003209 in RA is still vague. We aim to elucidate the role and its targeted microRNA of lncRNA HIX003209 in RA as ceRNA. Significantly increased expression of lncRNA HIX003209 was observed in the peripheral blood mononuclear cells (PBMCs) from RA cases. It was positively associated with TLR2 and TLR4 in RA. Besides, peptidoglycan (PGN) and lipopolysaccharide (LPS) could enhance the expression of lncRNA HIX003209, which reversely promoted the proliferation and activation of macrophages through IκBα/NF-κB signaling pathway. Moreover, HIX003209 was involved in TLR4-mediated inflammation via targeting miR-6089 in macrophages. LncRNA HIX003209 functions as a ceRNA and exaggerates inflammation by sponging miR-6089 through TLR4/NF-κB pathway in macrophages, which offers promising therapeutic strategies for RA.